Photosynthetic Oxygen Exchange in Isolated Cells and Chloroplasts of C(3) Plants - Furbank, Robert T. (1982)
Photosynthetic O(2)-production and photorespiratory O(2)-uptake were measured, using stable isotope techniques, in isolated intact leaf cells of the C(3) plant Xanthium strumarium L., and isolated intact chloroplasts of Spinacia oleracea L (var. Yates 102). Considerable light dependent O(2)-uptake was observed in both systems, a proportion of which could be suppressed by CO(2) (63% suppression in chloroplasts by 50 micromolar CO(2), 58% in cells by 100 micromolar CO(2) and 250 micromolar O(2)). At low O(2), O(2)-uptake was CO(2) insensitive. At high CO(2) up to 19% of total electron flow was to O(2) in cells and up to 14% in chloroplasts. O(2)-uptake showed inhibition by KCN (61% in cells, 35% in chloroplasts by 0.2 millimolar KCN). O(2)-uptake half saturated at 75 to 85 micromolar O(2) in cells and 50 to 65 micromolar O(2) in chloroplasts, at low CO(2). The results are discussed in terms of the RuP(2)-oxygenase reaction and direct photoreduction of O(2) via a Mehler reaction.